The impact of an online gamified approach embedded with self‐regulated learning support on students' reading performance and intrinsic motivation: A randomized controlled trial. (22nd May 2022) - Qiao, Shen; Chu, Samuel Kai Wah; Shen, Xiaoai; Yeung, Susanna Siu‐sze
Abstract: Background: Morphological awareness (MA) is the awareness and ability to manipulate morphemes, the smallest units of meaning in a language. It is identified as a strong cognitive precursor of word reading and reading comprehension. The current MA instructions are limited to classroom settings and delivered by teachers or experimenters. Few studies have included technology and its novel features to deliver MA instructions. Objectives: This study proposes a gamified learning approach embedded with self‐regulated learning support for MA learning and examines its effects on improving English reading performance and intrinsic motivation among junior secondary grade students who learn English as a foreign language. Methods: This study adopted a randomized controlled trial design. Participants ( N  = 104) were randomly assigned into one of three conditions: self‐regulated gamified programme, gamified programme, or non‐gamified programme. Students received 16 sessions of instructions (30 min/session) and were evaluated on reading abilities (i.e., MA, word reading and reading comprehension) and intrinsic motivation before and after the programme implementation. Results and conclusions: Results from repeated measures ANOVA and follow‐up ANCOVA showed that while the two gamified groups demonstrated greater improvement in MA (i.e., near transfer effect) and intrinsic motivation than non‐gamified group, only the self‐regulated gamified group showed more gains in multisyllabic word reading (i.e., far transfer effect) than non‐gamified group. There was no significant time X group interaction effect on reading comprehension. Implications: Taken together, this research suggests gamification leads to better morphology learning and increases students' intrinsic motivation. The incorporation of self‐regulated learning in gamification is recommended to achieve the far transfer effect on multisyllabic word reading. Lay Description: What is already known about this topic: Morphological awareness is an important reading‐related skill that predicts students' word reading and reading comprehension. However, existing morphological awareness instructions are mostly delivered by teachers or experimenters. Gamification, which is emerging as an effective approach that enhances learning and motivation, has not yet been widely applied to improve students' reading‐related skills, such as morphological awareness. Gamification is usually implemented in online learning environments where students' self‐regulated learning critically affects their online learning performance. However, few studies have provided self‐regulated learning support in a gamified learning environment. What this paper adds: We proposed a self‐regulated gamified approach specifically targeting morphological awareness and compared its effectiveness with gamified learning and non‐gamified learning. The two gamified groups led to significant gain in students' morphological awareness and intrinsic motivation than the non‐gamified group. Only the self‐regulated gamified group led to significant gain in multisyllabic word reading than the non‐gamified group. Implications for practice and/or policy: The self‐regulated gamified approach represents an effective way for learning morphological awareness.